Efficacy of five insecticides against bagworm, Metisa plana Walker and their side effects on oil palm pollinator, Elaeidobius kamerunicus Faust - Syed Mohamed, Syed Mazuan (2018)
Oil Palm (Elaeis guineensis Jacq.) is a crucial economic crop in Malaysia which has become susceptible towards pests and diseases. Studies showed that the major leaf defoliator of oil palm in Malaysia is the bagworm, Metisa plana. Various spraying methods had been developed for controlling the bagworms. Nonetheless, a large amount of insecticides applied were at waste due to either improper or no calibration conducted on the sprayers prior to application. The residual effects of insecticides on beneficial insects were highly concerned to preserve oil palm ecosystem. A ground study was conducted in FELDA Gunung Besout 04, Perak, with its main focus on mistblower application towards M. plana, and its side effects on Elaeidobius kamerunicus. Optimising in spraying application technique proved the effectiveness of the treatment by evaluating the operator’s walking speed, spraying swath width and droplet distribution. It was concluded that 40 seconds was the optimum time required for oil palm foliar sprayed with restrictor 3. Stihl SR420 mistblower was characterised by having 1.2L / min flow rate, produced volume median diameter of 80μm, and achieved productivity of approximately of 2.58 hectares per man day. The insecticides evaluated were chlorantraniliprole (Altacor® 34.9WG), Bacillus thuringiensis kurstaki (DiPel® ES), cypermethrin (Hextar Cyper 5.5EC), flubendiamide (Takumi® 20WG) and B. thuringiensis MPOB Bt1 (Ecobac-1 EC). The insecticides application rate was based on the manufacturer’s recommendation. The M. plana was monitored before treatment and at 3, 7, 15, 30, 45, and 70 days after treatment (DAT). Post-census showed that all insecticides were able to reduce the bagworm population below the economic threshold level (10 larvae/ frond) within 15 DAT. Both cypermethrin and MPOB Bt1 resulted in highest mortality of M. plana by 83%, followed by flubendiamide, chlorantraniliprole and Btk with mortality rate of 82%, 75%, and 70% respectively. The insecticides applied were able to suppress the population of M. plana up to 30 DAT. The side effect of insecticides on pollinating weevil, E. kamerunicus was also studied by monitoring the population before treatment and at 2, 4, 6 and 13 DAT. A sample population technique was designed to estimate the weevils population for every sample of male influorescence. Cypermethrin indicated the highest population declined at 2 DAT with a mortality of 92.33%, followed by B. thuringiensis, flubendiamide, and chlorantraniliprole with mortality of 44.50%, 30.62% and 18.19% respectively. Cypermethrin caused a significant reduction of weevil population. Whilst chlorantraniliprole, B. thuringiensis and flubendiamide displayed no significant reduction on the weevil population, which exhibit the characteristic of environmental friendly insecticides. Optimised mistblower application alongside the potential ecosystem friendly insecticides were recommended for sustainable control of bagworm population in oil palm.